Cross-cultural encounters in Polish and Russian travelogues about colonial Indonesia, 1870s-1910s - Ewertowski, Tomasz (Wacana, Journal of the Humanities of Indonesia, 2024)
This article explores cross-cultural encounters and identities discourses in selected Polish and Russian travelogues about the Netherlands East Indies. Poles and Russians could travel to the Netherlands East Indies thanks to advantages afforded Europeans by the colonial system. Their occupations (for example, a privileged tourist, colonial scientist, diplomat) often made them suitable imperial agents. They defined themselves as Europeans but, as Eastern Europeans, they occupied an ambiguous position: Russians came from a land-based, economically backward “empire of the periphery“ (Boris Kagarlitsky 2008); Poles came from a semi-peripheral European nation subjected to foreign rule and, from their common experience of subjugation, some Polish authors were able to sympathize with the colonized peoples. Hence, a comparative approach leads to various insights into representations of colonial Indonesia.